Usability Testing Pada Software Berhitung Berbasis Android Di Taman Kanak-Kanak Kecamatan Jagakarsa - Thomas Afrizal; Naely Farkhatin; Dwi Yulistyanti (STIKOM Tunas Bangsa Pematangsiantar, 2019)
True kindergarten is a place to play and learn for toddlers. From playing, children can learn to sharpen their brains and motor skills, so they are accustomed to playing and learning. Besides learning outside children can also learn through technology. Because technology can provide interactive and interesting learning for children. But only within learning. Implementation of android-based counting software can be used by children in terms of learning in counting. In previous research, this software has been implemented in kindergartens in the sub-district of Pejak. From the results of the implementation of the software can be seen the enthusiasm of children in terms of using the technology with the help of a device (Mobile). Children interact more with other children and children quickly and capable in calculating. The current research is assessing and testing the results of software that is used in kindergartens in the sub-district of Pejantan. In order to see what the advantages and disadvantages of the software. in assessing and testing the software researchers used usabillity testing to test it. This is because usability testing is easy to use and test. So that the results can be quickly seen. From the application of usabillity testing this research can be produced as a whole good and friendly to the user.